Management information systems for the information age - Haag, Stephen (McGraw-Hill, 2004)
This book contains chapters that cover what instructors want students to know about MIS while Extended Learning Modules (XLMs) show students what they can do with MIS. This book features a contemporary writing style and a wealth of examples that engage students like no other MIS text. Arranged with chapter opening cases that highlight how an organization has successfully implemented many of the chapter's concepts, and chapter closing cases that help students apply what they just learned, gives students the hands-on knowledge that is applicable in both their personal and professional experiences